2021
DOI: 10.48550/arxiv.2104.02182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Majorana correlations in the Kitaev model with ordered-flux structures

Akihisa Koga,
Yuta Murakami,
Joji Nasu

Abstract: We study the effects of the flux configurations on the emergent Majorana fermions in the S = 1/2 Kitaev model on a honeycomb lattice, where quantum spins are fractionalized into itinerant Majorana fermions and localized fluxes. A quantum spin liquid appears as the ground state of the Kitaev model in the flux-free sector, which has intensively been investigated so far. In this flux sector, the Majorana fermion system has linear dispersions and shows power law behavior in the Majorana correlations. On the other … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…With the energy spectrum found in the expression (31) We also observed that when the parameter k increases, the mean energy U/N increases with an approximately linear behavior close to the origin, i. e., T = 0. However, when T increases, the behavior of the energy starts to be more distinct.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…With the energy spectrum found in the expression (31) We also observed that when the parameter k increases, the mean energy U/N increases with an approximately linear behavior close to the origin, i. e., T = 0. However, when T increases, the behavior of the energy starts to be more distinct.…”
Section: Resultssupporting
confidence: 63%
“…In particular, we believe that studying Majorana fermions can help us better understand the behavior of these relativistic particles. In fact, once we understand the behavior of these particles better, we are able to comprehensively understand some physical phenomena, e. g., the dynamic of quantum spin liquid which has been widely studied [31][32][33][34] to understand spin transports in quantum spin systems and are applied in spintronic contexts [35]. In addition, to understand the properties of Majorana's fermions allow us to know a little more about the thermodynamics associated with topological insulators and the Majorana's superconductivity [36], which can leads to semiconductor nanowires [37] and to a revolution in the industry of electrical devices [38].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since low-lying itinerant Majorana fermions does not induce magnetic excitations in the bulk, longrange spin transport is expected to be retained even in the presence of magnetic impurities. It is also interesting to examine Majorana correlations in the present system [50], which is beyond the scope of our study.…”
Section: Resultsmentioning
confidence: 99%